Construção social de mercados e as tendências de consumo: o caso do Pavilhão da Agricultura Familiar da EXPOINTER (RS) - Maycon Schubert; Sergio Schneider (Ciências Sociais Unisinos)
The article explores the contexts of social construction of markets, focusing on the family farmers’ market at EXPOINTER (Brazil) as research topic. The main goal is to discuss the historical development of this marketplace by using a methodology based on semistructured interviews with key actors, social movements and public officials. Besides, a questionnaire with closed questions was applied to 218 buyers/consumers to gather information on their profile. The family farmers’ market exists since 1999 within EXPOINTER as a fair and takes place annually. The analysis showed that the buyers/consumers at the fair have a high income and educational level. The findings showed that the products from the family farmers have a great receptivity among consumers because of their quality as well as due to a sense that they contribute to health. The study also concluded that the fair was created by a coalition of interest by the government and social movements, especially the rural trade unions of family farmers.